Analisis Editing Video Broadcast Pada Acara Berita TVRI Sumatera Utara - Abdullah Afif Baihaqi; Yusuf Ramadhan Nasution; Awal Rizki Siregar (Universitas Katolik Widya Karya Malang, 2023)
. In the ever-growing information era, video editing has become an important part of television news production. This study investigates the use of video editing on TVRI North Sumatra news programs. This research focuses on the editing software used, the editing methods used, and how the use of this editing impacts the quality of news production. To gain a better understanding of video editing techniques at regional news stations, we conducted direct observations, interviews, and document analysis through qualitative research methods. The research results show that video editing at TVRI North Sumatra is carried out by professional programs. To improve the visual and audio quality of news broadcasts, adjustment techniques such as visual transitions, color adjustments, and sound effects are often used. In the use of broadcast video editing, issues such as limited time and resources are identified as important elements. Improved time management, more training for production teams, and more technical resources are recommended. In other words, this research provides a comprehensive analysis of video editing methods in TVRI North Sumatra news production. The results could improve the industry's understanding of video editing methods in regional news contexts and help develop more creative and high-quality news production methods.